A prediction model for sulcus-to-sulcus diameter in myopic eyes: a 1466-sample retrospective study - Zhu, Qiu-Jian; Zhu, Wei-Jian; Chen, Wen-Jing; Ma, Lie; Yuan, You (BMC ophthalmology, 2022)
Background To establish and verify the accuracy and reliability of a sulcus-to-sulcus diameter (STS) prediction model. Methods In this retrospective study, the prediction formula was established with the data from 1466 eyes from 733 subjects from July 2020 to April 2021 and verified with the data from 278 eyes from 139 subjects between May 2021 and June 2021. Each subject was measured with a Pentacam, IOLMaster 700, OPD-Scan III, and ultrasound biomicroscope. The prediction formulas were established with multiple linear regression, and intergroup correlation coefficients (ICCs) and Bland-Altman tests were used to assess the agreement between the predicted and actual STS (actual STS was measured by UBM). Results The explanatory variables relevant to the horizontal STS (STSH) were the Pentacam white-to-white diameter (WTWP; standardized partial regression coefficient [[beta]] = 0.330; p < 0.001), the flat K value ([beta] = -0.211; p < 0.001), and the anterior corneal diameter (ACD) ([beta] = 0.178; p < 0.001). The corresponding multiple regression equation was : STSH (mm) = 8.061 + 0.510 x WTWP - 0.090 x Flat K value + 0.430 x ACD. The explanatory variables relevant to the vertical STS (STSV) were the WTWP ([beta] = 0.435; p < 0.001), the steep K value ([beta] = -0.271; p < 0.001), and the ACD ([beta] = 0.187; p < 0.001). The corresponding multiple regression equation was : STSV (mm) = 8.540 + 0.492 x WTWP - 0.075 x Steep K value + 0.329 x ACD. The bias of the predicted to the actual STSH was - 0.021, with 95% limits of agreement (95% LoA) from - 0.499 to 0.457. The bias of the predicted to the actual STSV was 0.057, with 95% LoA from - 0.462 to 0.575. The ICC was 0.883 between the predicted and actual STSH and 0.859 between the predicted and actual STSV. Conclusions The Pentacam-measured WTW, the K value and the ACD are important for predicting the STS diameter. The prediction model has good accuracy and reliability. Trial registration Not applicable. Keywords: WTW, STS, Prediction model, Bland-Altman test